Comparative Analysis of Consumer Perceptions of Indomaret Minimarkets and Planet 2000 Supermarkets in Ambon City - Sapulette, Alvian -; Hursepuny, Harold -; Salhuteru, Andrie Ch (Politeknik Negeri Semarang, 2023)
This study aims to determine whether there are differences in perceptions between consumers of Indomaret minimarkets and Planet 2000 supermarkets. This research was conducted in Ambon City, Maluku Province. Researchers collected data using interview and questionnaire techniques. The population in this study were Ambon city residents who had shopped. The sample used was respondents who had already been and respondents who were temporarily shopping. While the sample in this study was divided into two groups, namely a sample of Indomaret minimarket customers and a sample of Planet 2000 supermarket customers, each represented by 50 respondents. Sampling using Non Probability Sampling technique with Convenience Sampling type. The data analysis technique used is Likert scale analysis, and mean difference analysis for unpaired data. The results of this study indicate that the characteristics of Indomaret minimarket respondents are mostly male, aged between 25-35 years, working as entrepreneurs, and with incomes ranging from Rp 3,000,000.00 - Rp 5,000,000.00. While the characteristics of Planet 2000 supermarket respondents are mostly female, over 35 years old, high school graduates, working as teachers/lecturers, with incomes above Rp 5,000,000.00. The results of this study also show that there are differences in perceptions about the services of Indomaret minimarkets and Planet 2000 supermarkets.